(untitled) (International Journal of Engineering and Computer Science, 2020)
These days technology plays enormous roles in making day to day human activities easier. Previously established institutions need to reconstruct their data centers to run their business in an easy and comfortable manner. information and communication technologies (ICT) used for progressive improvement in the quality of education. in most developing country education disseminate rate is low with different factors poor of infrastructure, well engaged and capable teachers, geographical locations, different education tools, laboratories and also budgeting issues are the main challenges, as government higher education can invest more budget and they can deploy different clouds for a society at least one public university in one state have responded to deploy a cloud. they can distribute centrally different educational information’s, books, and so on, again not expected that all schools are developing their own datacenter and full fill different computing infrastructure’s which cost more instead with this scenario all schools including primary, secondary and university’s mostly fourth-generation universities since they may take a lot of time to deploy their infrastructures until they can use another’s universities cloud minimizing costs and manpower.